Possibilities of neurophysiological methods of study in encephalopathy of occupational and non-occupa-tional genesis - E. V. Katamanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The diagnostic possibilities of the neurophysiological study methods were studied in the process of examining the patients with chronic mercury intoxication, discirculatory encephalopathy and chronic alcoholism to reveal the disorders of the bioelectrical activity, indicating the organic brain injury in the encephalopathy of the occupational and non-occupational genesis. 36 patients with the postponed chronic mercury intoxication (CMI) working at the chemical enterprise in shop on manufacture soda and chlorine a method mercury electrolyses (group I) were chosen for study. The average age of the patients in this group was 50,8 ± 6,0, average work period -14,7 ± 1,05years. The second group consisted of 30 patients with discirculatory encephalopathy (DE) (average age - 50,8 ± 5,2 years old). The third group consisted of 30 persons with chronic alcoholism (average time period of the alcoholization was 16,7 ± 2,1 years, average age - 47,5 ± 6,6 years old). The control group consisted of 30 practically healthy men (average age - 50,8 ± 5,2 years old, average total working period -14,2 ± 1,2 years) who were not occupationally exposed to the harmful substances (group IV). The persons examined in all the groups were males. The complex analysis of the available neurophysiological indices allowed to reveal the expression of the brain deficiency, to assess the specificity of the disorders revealed in the encephalopathies of different genesis. The multinidus brain injuries were revealed indigently of the etiological factor in encephalopathies. The presence of the equivalent sources of pathological activity in the field of the dyencefalic structures which may be clinically characterized by the emotional and cognitive disorders was found to be a common sing. The injury of the corny body was considered as the specific character for mercury-induced encephalopathy evidenced by the presence of the expressed depressive responses. More frequent presence of the pathological nidus activity in the cerebellar field which were clinically followed by the cerebellar disorders were presented as the characteristic difference for alcohol encephalopathy. The temporal brain regions were considered as the more typical source of the pathological activity in the discirculatory encephalopathy.